An EXAFS spectroscopic study of Am(III) complexation with lactate - Fröhlich, Daniel R.; Skerencak-Frech, Andrej; Koke, Carsten; Panak, Petra (Journal of synchrotron radiation, 2015)
The pH dependence (1-7) of Am(III) complexation with lactate in aqueous solution is studied using extended X-ray absorption fine-structure (EXAFS) spectroscopy. Structural data (coordination numbers, Am—O and Am—C distances) of the formed Am(III)-lactate species are determined from the raw k3-weighted Am LIII-edge EXAFS spectra. Between pH 1 and pH 6, Am(III) speciation shifts continuously towards complexed species with increasing pH. At higher pH, the amount of complexed species decreases due to formation of hydroxo species. The coordination numbers and distances (3.41-3.43 Å) of the coordinating carbon atoms clearly point out that lactate is bound `side-on' to Am(III) through both the carboxylic and the α-hydroxy function of lactate. The experimentally determined coordination numbers are compared with speciation calculations on the basis of tabulated thermodynamic stability constants. Both EXAFS data and thermodynamic modelling are in very good agreement. The EXAFS spectra are also analyzed by iterative transformation factor analysis to further verify the determined Am(III) speciation and the used structural model.
Gesehen am 05.08.2021